Relevansi Politik Identitas Pemilih Muslim dalam Pemilihan Gubernur Sumatra Utara Tahun 2018 - Dharma Kelana Putra (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2019)
The similarity of identity such as religion and ethnicity as a primordial aspect becomes a preference in choosing a leader not based on their capability. In the election of the Governor of North Sumatra in 2018, identity politics tended to strengthen in Muslim voters, especially in terms of religion, indigenous issues and natives. This practics of identity politics resulted in a victory for the couple Edy Rahmayadi-Musa Rajeckshah (Islam-Islam). The main question in this study is why identity politics is still relevant to be used by Muslim voters in the Election of Governor of North Sumatra in 2018. The study was conducted with a qualitative descriptive method, in which all data were collected through library studies and internet searching. This study concludes that Muslim voters see identity politics still relevant to use in choosing leaders because they consider Muslims have to be led by leaders who care about Islam. This understanding emerged from previous experiences in DKI Jakarta, namely the Al Maidah 51 incident by Ahok and discriminatory practices against Muslims when led by the non-Muslims and the Muslims who did not care about Islam in various regions in Indonesia